Caracterização estrutural e avaliação das atividades farmacológicas da fucana B extraída da alga Dictyota menstrualis - Costa, Thiago Gomes (2014)
Seaweeds are a major source of biologically active compounds . In the extracellular matrix of these organisms are sulfated polysaccharides that functions as structural components preventing it against dehydration. The fraction 0.9 (FucB) rich in sulfated fucans obtained from brown seaweed Dictyota menstrualis was chemical characterized and evaluated for pharmacological activity by testing anticoagulant activity, stimulatory action on the synthesis of an antithrombotic heparan sulfate, antioxidant activity and its effects in cell proliferation. The main components were FucB carbohydrates (49.80 ± 0.10 %) and sulfate (42.30 ± 0.015 %), with phenolic compounds ( 3.86 ± 0.016 %) and low protein contamination ( 0.58 ± 0.001 % ) . FucB showed polydisperse profile and analysis of signals in the infrared at 1262, 1074 and 930 cm -1 and 840 assigned to S = O bonds sulfate esters , CO bond presence of 3,6- anhydrogalactose , β -D- galactose non- sulfated sulfate and the axial position of fucose C4 , respectively. FucB exhibited moderate anticoagulant activity , the polysaccharides prolonged time (aPTT ) 200 ug ( > 90s ) partial thromboplastin FucB no effect on prothrombin time (PT), which corresponds to the extrinsic pathway of coagulation was observed. This stimulation promoted fraction of about 3.6 times the synthesis of heparan sulfate (HS) by endothelial cells of the rabbit aorta ( RAEC ) in culture compared with cells not treated with FucB . This has also been shown to compete for the binding site with heparin. The rich fraction sulfated fucans exhibited strong antioxidant activity assays on total antioxidant (109.7 and 89.5 % compared with BHT and ascorbic acid standards ) , reducing power ( 71 % compared to ascorbic acid ) and ferric chelation ( 71 , comparing with 5 % ascorbic acid). The fraction of algae showed cytostatic activity on the RAEC cells revealed that the increase of the synthesis of heparan sulfate is not related to proliferation. FucB showed antiproliferative action on cell lines modified as Hela and Hep G2 by MTT assay . These results suggest that FucB Dictyota menstrualis have anticoagulant , antithrombotic , antioxidant potential as well as a possible antitumor action, promoting the stimulation of the synthesis of antithrombotic HS by endothelial cells and is useful in the prevention of thrombosis, also due to its inhibitory action on species reactive oxygen ( ROS ) in some in vitro systems , being involved in promoting a hypercoagulable state